2010
DOI: 10.1111/j.1365-2265.2010.03871.x
|View full text |Cite
|
Sign up to set email alerts
|

Superior discriminating value of ACTH‐stimulated serum 21‐deoxycortisol in identifying heterozygote carriers for 21‐hydroxylase deficiency

Abstract: This study confirms the superiority of ACTH-stimulated 21DF, when compared to 17OHP, both measured by LC-MS/MS, in identifying carriers for 21OHD. Serum 21DF is a useful tool in genetic counselling to screen carriers among relatives in families with affected subjects, giving support to molecular results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
5
33
0
2
Order By: Relevance
“…The high diagnostic value of 21-deoxycortisol has previously been observed by others [41] and by us [42], confirming our conclusion. In contrast, the 17-hydroxyprogesterone MoM cutoff alone – although sensitive – is not specific for 21OHD, since it can be elevated in ACC and in obesity as well.…”
Section: Discussionsupporting
confidence: 82%
“…The high diagnostic value of 21-deoxycortisol has previously been observed by others [41] and by us [42], confirming our conclusion. In contrast, the 17-hydroxyprogesterone MoM cutoff alone – although sensitive – is not specific for 21OHD, since it can be elevated in ACC and in obesity as well.…”
Section: Discussionsupporting
confidence: 82%
“…The Janzen et al (21) study thus supports our present strategy of including 21S and cortisol rather than 17OHP/DOC for sensitive and specific detection of the carrier status. We also did not find the significant correlation between 17OHP and 21S published by Costa-Barbosa et al (23). This is possibly due to the fact that we only studied asymptomatic heterozygous carriers instead of non-classic CAH patients.…”
Section: Discussionmentioning
confidence: 37%
“…Besides the usefulness of 21-Deox determination in differential diagnostics, the results of an earlier study suggested that 21-Deox might be superior to 17-OHP in the identification of heterozygote carriers for a 21-OH deficiency following an adrenocorticotropic hormone stimulation test [25]. The true value of this latter observation is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 94%